Corporate brand building at SRF: challenge of selecting the brand consultant. Issue 4 (27th January 2016) - Mukherjee, Jaydeep; Trivedy, Mukund
Abstract : Title: – Corporate brand building at SRF: challenge of selecting the brand consultant. Subject area: – The case is about the selecting the agency to take up the brand building challenge of SRF Limited, a well established, large business in India having diverse lines of "industrial products". The business decision problem of SRF stemmed from the fact that the corporate leadership team, which had to take a decision on the topic had considerable reservation about the appropriateness of each of short-listed agencies for the job at hand. There were also differences of opinion on what would be the criteria for selecting the brand consultant. The Managing Director had to ensure that the team arrived at a consensus, rather than being foisted with a decision from top. Study level/applicability: – This case can be taken up in executive education programs as well as the basic marketing management program at the postgraduate level or in a specialist advertising courses. The case can be taught in the core marketing course at the postgraduate level while discussing the selection on advertising agency. Case overview: – The decision-making focus of the case is about selecting an advertising agency among a set of three, which was most suited to help SRF achieve the repositioning, branding and the awareness creation challenge. The agencies, however, were mostly experienced in building brands for consumer product which was distinct from industrial intermediaries company like SRF. As an organization, SRF had no experience of dealing with an advertising agency, thus the selection was quite a challenge. It brings to focus the decision-making dilemma faced by a large number of companies in emerging markets which are making the transition to brand building. Expected learning outcomes: – The following insights could be elucidated by the case:Help the students understand the corporate branding concept as distinct from product branding. Decision-making dilemmas associated with corporate brand building for a company with long legacy of product branding.Criteria for evaluating the proposals by advertising agency from the perspective of a client organization. Supplementary materials: – Teaching notes.